Efficacy of medical thoracoscopy combined with fibrinolytic therapy in the treatment of complicated parapneumonic effusions and empyema - Feng-Fu Zhan; Mao-Hong Huang; Yan-Ping Du; Yan Chen; Han-Han Chen; Yi-Li Lin; Yi-Yuan Chen; Ling Cai; Xiao-Bin Zhang (BMC Pulmonary Medicine)
Abstract Objective This study aimed to evaluate the clinical efficacy, safety, and feasibility of medical thoracoscopy combined with fibrinolytic therapy for the treatment of complicated parapneumonic effusions and empyema, with a focus on therapeutic outcomes and recovery duration. Methods A retrospective cohort study was conducted involving 108 patients treated at Zhongshan Hospital, Xiamen University, between January 2015 and May 2024. Patients were categorized into two groups: the medical thoracoscopy group (n = 33) and the traditional treatment group (n = 75). The thoracoscopy group underwent thoracoscopic adhesiolysis and loculation breakdown, followed by intrapleural urokinase administration. The traditional treatment group received pleural catheter drainage combined with urokinase therapy. Primary outcomes included changes in inflammatory markers (white blood cell count, C-reactive protein, and procalcitonin), imaging outcomes (resolution of pleural effusion, pulmonary inflammation, and the incidence of pleural thickening at three months), pulmonary function assessed by forced vital capacity (FVC), and in-hospital mortality. Secondary outcomes encompassed the duration of postoperative fever, drainage time, intravenous antibiotic use, complication rates, initial treatment failure, length of hospital stay, and hospitalization costs. Results Both groups demonstrated significant reductions in inflammatory markers post-treatment (P < 0.05). Pleural effusion resolution, pulmonary inflammation reduction, and the incidence of pleural thickening at three months were comparable between the groups (P > 0.05). Improvements in FVC were observed in both groups, with significantly greater gains in the thoracoscopy group (P < 0.05). No in-hospital mortality was reported. Compared to the traditional treatment group, the thoracoscopy group exhibited significantly lower postoperative inflammatory marker levels (P < 0.05), alongside shorter durations of postoperative fever, pleural drainage, intravenous antibiotic use, and hospital stay (all P < 0.05). The thoracoscopy group also had a significantly lower initial treatment failure rate (P < 0.05). Complication rates and hospitalization costs were comparable between the groups (P > 0.05). Conclusions Medical thoracoscopy combined with fibrinolytic therapy offers significant advantages in the management of complicated parapneumonic effusions and empyema. This approach effectively enhances inflammation control, improves pulmonary function, and accelerates recovery time without compromising safety or increasing costs, underscoring its potential for broader clinical application.